1997
DOI: 10.1074/jbc.272.12.8071
|View full text |Cite
|
Sign up to set email alerts
|

Identification, Characterization, and Tissue Distribution of Human Peroxisome Proliferator-activated Receptor (PPAR) Isoforms PPARγ2 versus PPARγ1 and Activation with Retinoid X Receptor Agonists and Antagonists

Abstract: We describe the cloning, characterization, and tissue distribution of the two human peroxisome proliferator activated receptor isoforms hPPAR␥2 and hPPAR␥1. In cotransfection assays the two isoforms were activated to approximately the same extent by known PPAR␥ activators. Human PPAR␥ binds to DNA as a heterodimer with the retinoid X receptor (RXR). This heterodimer was activated by both RXR agonists and antagonists and the addition of PPAR␥ ligands with retinoids resulted in greater than additive activation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
265
2
3

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 385 publications
(279 citation statements)
references
References 40 publications
9
265
2
3
Order By: Relevance
“…Our results contrast to initial studies in which expression of PPAR-␥ gene and protein in the human kidney was not detected (18,19). However, subsequently, PPAR-␥ has been confirmed in human kidney (20,21), and several groups have since identified the presence of PPAR-␥ message and protein in major components of the glomerulus, in mesangial cells, and in endothelial cells in animal models (9,22,23).…”
Section: Discussioncontrasting
confidence: 56%
“…Our results contrast to initial studies in which expression of PPAR-␥ gene and protein in the human kidney was not detected (18,19). However, subsequently, PPAR-␥ has been confirmed in human kidney (20,21), and several groups have since identified the presence of PPAR-␥ message and protein in major components of the glomerulus, in mesangial cells, and in endothelial cells in animal models (9,22,23).…”
Section: Discussioncontrasting
confidence: 56%
“…Interestingly, there are three putative PPREs in the 5Ј flanking sequence of UCP3. Peroxisome proliferator-activated receptor (PPAR)-␣ and PPAR-␥1 are expressed in skeletal muscle (39). PPAR ligands include a variety of long-chain fatty acids and their derivatives (40).…”
Section: Discussionmentioning
confidence: 99%
“…PPAR-γ agonists (i.e. thiazolidinediones) exert their metabolic effects by binding to the PPAR-γ receptor, which is located primarily on the adipocytes [15]. Previous studies from our laboratory [16,17] and others [18,19] have demonstrated that thiazolidinedione (PPAR-γ agonists) treatment in patients with type 2 diabetes mellitus is associated with a reduction in plasma NEFA levels and NEFA turnover, a shift in fat distribution from visceral and hepatic to subcutaneous depots, improved hepatic and peripheral (muscle) insulin sensitivity and enhanced insulin signalling.…”
Section: Introductionmentioning
confidence: 99%